2019
DOI: 10.4236/wjet.2019.71002
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic Boxing Glove Reduces Upward Drift in Peak Force and Loading Rate over a Long Series of Impacts

Abstract: A conventional boxing glove and a prototype pneumatic glove were each fitted to a mechanical fist and dropped 253 times from a height of 3 metres on to a force plate covered by an ethylene vinyl acetate (EVA) mat. Impact dynamics were measured and modelled. From the outset, peak impact force and peak rate of force development (loading rate) were lower for the pneumatic glove. For both gloves, these variables displayed upward drift during the drop series, but the drift was smaller for the pneumatic glove. Conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In a previous publication reporting on data that did not incorporate glove velocity measures, we noted that force plate contact time was the best predictor of peak impact force for a conventional 10 oz glove while time from initial force plate contact to occurrence of peak force was the best predictor for an ARLI glove [4]. Figure 22 shows that in the current study, too, these variables were strong predictors of peak impact force for each individual glove type, with R 2 values always exceeding 0.96.…”
Section: Relationship Of Peak Glove Deceleration During Compressive Pmentioning
confidence: 76%
See 3 more Smart Citations
“…In a previous publication reporting on data that did not incorporate glove velocity measures, we noted that force plate contact time was the best predictor of peak impact force for a conventional 10 oz glove while time from initial force plate contact to occurrence of peak force was the best predictor for an ARLI glove [4]. Figure 22 shows that in the current study, too, these variables were strong predictors of peak impact force for each individual glove type, with R 2 values always exceeding 0.96.…”
Section: Relationship Of Peak Glove Deceleration During Compressive Pmentioning
confidence: 76%
“…A question arises, however, as to whether there are other contributors to peak force reduction. In one of our published experiments [4], we found that over a series of 250 drops on to a force plate from a height of 3 metres there was progressive upward drift in peak force and loading rate for both a pneumatic glove and a conventional 10 oz glove, with the magnitude of drift less for the pneumatic glove. In the case of the conventional glove, ~96% of the variance in peak force could be explained by variance in contact time, with peak force increasing as contact time decreased.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations